The kanawha county school dropout problem, 1962-63 - Peck, Hugh I.; Kanawha County Schools, Charleston, WV. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1963)
Factors contributing to high school dropouts were investigated. IQ and previous grade were examined, 23.8 percent of the dropouts questioned indicated lack of interest as the primary reason for leaving school. Another 13.4 percent indicated parental lack of interest, while 15.3 percent indicated discouragement through course failure. Nine characteristics studied were--sex, education and occupation of father, socioeconomic status of the family, scholastic aptitude, reading level, arithmetic level, years retained, days absent to grade six. It was found that two periods when dropouts are heaviest are the summer months and January. The largest number of dropouts are 16 years of age. More boys than girls drop out of school. Scholastic aptitude is lower in the dropout than in the persister. Reasons for dropping out were related to home situations, which were more unfortunate than those of the persister. Occupational classification of the father emerged as a significant factor, as few dropouts came from families where the fathers were classified as professional, sales or service. Identification of a school dropout as early as his seventh grade seems possible. Results indicate that he will most likely be a boy of below average intelligence, with reading and math achievement well below average. He will have been detained one or more years and have a poor attendance record. His father will have below an eighth-grade education and/or be unemployed, on welfare and/or of unskilled occupation.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Ability; Dropout Characteristics; Dropout Research; Motivation